2022
DOI: 10.1038/s41419-022-04786-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeted P2X7/NLRP3 signaling pathway against inflammation, apoptosis, and pyroptosis of retinal endothelial cells in diabetic retinopathy

Abstract: Retinal endothelial cells (RECs) are the primary target cells for diabetes-induced vascular damage. The P2X7/NLRP3 pathway plays an essential role in amplifying inflammation via an ATP feedback loop, promoting the inflammatory response, pyroptosis, and apoptosis of RECs in the early stages of diabetic retinopathy induced by hyperglycemia and inflammation. 3TC, a type of nucleoside reverse transcriptase inhibitor, is effective against inflammation, as it can targeting formation of the P2X7 large pore formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Kong et al. found that targeting the P2X7/NLRP3 signaling pathway prevents retinal endothelial cell pyroptosis in diabetic retinopathy ( 139 ). Kasson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al. found that targeting the P2X7/NLRP3 signaling pathway prevents retinal endothelial cell pyroptosis in diabetic retinopathy ( 139 ). Kasson et al.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of P2X7R can promote the formation of NLRP3 inflammasome [ 16 , 17 ], which is an intracellular multimeric protein complex that initiates inflammatory response and cell death (pyroptosis and apoptosis) by activating its effector caspase-1 [ 18 20 ]. The active caspase-1 facilitates the production of proinflammatory cytokines IL-1β and IL-18 [ 21 23 ], and activates pyroptosis-related protein Gasdermin D (GSDMD) and apoptosis-related protein caspase-3 [ 24 – 26 ]. This may lead to gliosis, neuronal loss and white matter damage, consequently leading to cognitive impairment [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is known to be a major contributor to endothelial cell death [ 11 , 12 ]. However, several studies have pointed out that apoptosis itself cannot explain all the endothelial loss processes, making exploring new forms of cell death urgently needed [ 13 15 ]. Ferroptosis is a newly identified nonapoptosis cell death, characterized by lethal accumulation of intracellular iron and iron-induced lipid reactive oxygen species (ROS) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%